Foreign Students’ Common Problems in Writing Chinese Characters - Razali, Norlida (WILAYAH: The International Journal of East Asian Studies, 2015)
Chinese characters belong to the ideographic system and are widely different from phonetic writing. Chinese characters are hard to remember, difficult to write and identify and as such these features have become major obstacles in learning Chinese by foreign students. Therefore, in view of this, it is necessary to research common problems in writing Chinese characters among foreign students and to provide suggestions to solve common problems. It is expected that this study will provide students with a reference to improve writing skills as well as promote interest in learning Chinese. In addition, this research hopes students will be able to correct common errors and learn more effectively. Chinese characters are very unique, with deep cultural connotations, which makes foreigners interested in wanting to learning it, but due to the complex structures of Chinese characters and the diversity, it is extremely difficult for foreign students to learn Chinese characters. This paper starts by discussing common problems encountered by beginners when writing Chinese characters within the context of shape, sound and meaning. Next, it highlights the reasons for errors and puts forward some learning strategies.